The relationship of information disclosure on compliance with Malaysian Financial Reporting Standard (MFRS) of listed telecommunication companies in Malaysia / Halwani Abd Azis - Abd Azis, Halwani (2017)
This study is conducted to analyze the level of compliance on information disclosure with respect to Malaysian Financial Reporting Standard of listed telecommunication companies in Malaysia. Telecommunication companies been chosen in this study as nowadays telecommunication industry experienced higher competitive advantage as to compare with other industry. Apart from that, telecommunication companies have move forward and expand successfully. The independent variables are company attributes such as size, profitability and debt equity. While, level of mandatory information disclosure compliance with MFRS as the dependent variable. The analyzation taking samples that consist of thirteen telecommunications companies and the data was collected between 2011 until 2015.